Functional characteristics of woody plants photosynthetic system in technogenic conditions - Tulkova, Elena G. (Journal of the Belarusian State University. Ecology, 2019)
The article investigates the adaptive reactions of the most common Gomel city woody plants of three age groups in their technogenic conditions growth. The silver birch Betula pendula Roth. and maple acuminous Acer platanoides L. in all age groups is characterized by less effective functioning of the photosynthetic apparatus at a higher pigments concentration under the technogenic conditions. Small-leaved linden Tilia cordata Mill. demonstrates a tendency to reduce the photosynthesis pigments concentration in technogenic environment, to reduce here the magnitude of fluorescence photochemical quenching and the growth of thermal energy dissipation, which can adversely affect the survival of plants under the industrial emissions influence. Lombardy poplar Populus pyramidalis Roz. in the studied age categories is characterized by various changes in the photosynthetic apparatus functioning, so at this stage any unambiguous trend of adaptive strategy could not be identified.
Keywords: birch hanging Betula pendula Roth.; norway maple Acer platanoides L.; lombardy poplar Populus pyramidalis Roz.; small-leaved linden Tilia cordata Mill.; photosynthetic pigments; photosynthesis activity